The infernal machine : a history of terrorism - Carr, Matthew ([S.l.] : The New Press, 2007)
A dramatic reframing of our troubled present against a century full of striking historical parallels. In 1881, a small group of Russian revolutionaries calling themselves "terrorists" assassinated Tsar Alexander II in a spectacular bombing attack in St. Petersburg. Far from being psychopathic murderers, these men and women viewed their actions as a just response to tyranny. The violence in Russia launched a crucial but poorly understood chapter in modern political history. With extraordinary narrative sweep, investigative journalist Matthew Carr unearths the complex realities of terrorist violence and its indelible impact on nations as different as Italy, Argentina, France, Algeria, Ireland, Russia, Japan, and the United States. Spanning over a century of world history, The Infernal Machine reveals stunning similarities in societies' responses to terrorism despite profound political and cultural differences. Again and again, Carr demonstrates that the true impact of terrorism has been felt in the overreactions of government and the media to acts of political violence, as rulers have consistently seized on terrorist attacks as a pretext for a massive counterassault, sacrificing civil liberties and curtailing democratic institutions in the name of security. Includes historical accounts of: IRA, Mau Mau, Red Brigades, Baader-Meinhof Gang, PLO, National Liberation Front of Algeria, The Weathermen, ETA/Basque separatists, Carlos the Jackal, Hezbollah, The Tamil Tigers, Al-Qaeda.
Keywords: Terrorism